The influence of religion and state ownership on CSR disclosure quality: A case of the pharmaceutical industry in China / Tian Tian - Tian, Tian (2021)
A growing amount of research has identified the importance of the institutional environment in determining the companies’ CSR disclosure (CSRD). This perspective suggests that companies in any society facing both formal and informal institutional constraints that they must follow to gain legitimacy. Hence, this research provides insights into the CSRD quality by considering the vital role of institutional constraints. Specifically, the primary purpose of this research is to investigate the influence of religion, representing an informal institution, on the CSRD quality. Additionally, the study identifies the effect of different religions on the CSRD quality. Further, the study also examines how state ownership, representing a formal institution, moderates the relationship between religion and the CSRD quality. The investigation focuses on the pharmaceutical industry in China, an ancient country where religion has an impact on the life of the society. The country is also the leading producer and consumer in pharmaceutical products. Thus, the decisions (including CSRD) of the pharmaceutical companies have a significant impact on both domestic and international stakeholders. This research is conducted by employing the panel data regression method. The results demonstrate that pharmaceutical companies with the higher CSRD quality are positively correlated with religion, which weakens when the state owns these companies, indicating that state ownership moderates the relationship between religion and the CSRD quality. Further, the findings suggest that Buddhism, Taoism, and Catholicism are found to be positively related to the CSRD quality, whereas Islam and Protestantism are not associated with the CSRD quality. The findings of this research contribute theoretically to understanding the influence of religion and state ownership on the CSRD quality in the pharmaceutical industry in China. Practically, the findings established in this study provide evidence on determinants of the CSRD quality in China’s pharmaceutical companies that can assist various stakeholders (managers of pharmaceutical companies, investors, regulators, and the public) in making relevant economic decisions.